The Influence of Work Ethos and Work Discipline on Employee Performance at the Social Affairs Office of North Maluku Province - Tjan, Ardiansya Edy; Nurlaila, Nurlaila; Buamonabot, Irfandi (International Journal of Business, Law, and Education, 2026)
This study aims to analyse the influence of work ethos and work discipline on employee performance at the Social Affairs Office of North Maluku Province. A quantitative approach was employed, involving 61 employees selected through a saturated sampling technique. Data were analysed using multiple linear regression with SPSS version 26. The results of the t-test indicate that both work ethos and work discipline have positive and statistically significant partial effects on employee performance. Furthermore, the F-test results confirm that these variables simultaneously influence employee performance with a high level of significance (F = 124.248). These findings imply that strengthening internal professional values alongside enforcing organisational regulations plays a critical role in improving the quality of public services. This study recommends that management continuously prioritize human resource development through systematic supervision and motivational strategies.